The Influence of Freeze-Thaw Cycles on the Mechanical Properties of Loess Under Temperature Variations - Fang Zheng; Xinle Xue; Zhanping Song; Yuwei Zhang; Hongke Liu (Buildings)
Freeze-thaw (F-T) cycle tests and triaxial shear tests are conducted under varying freezing ambient temperatures and different F-T cycles for remolded loess. The results indicate that nearly all stress–strain curves of remolded loess exhibit strain-hardening behavior under varying freezing ambient temperatures and different F-T cycles. A decrease in freezing temperature alters the yield strain of loess and diminishes its resistance to deformation. As the freezing temperature decreases and the number of F-T cycles increases, the failure deviatoric stress of loess initially decreases, then increases, and eventually stabilizes. The most detrimental freezing temperature is −12 °C, which significantly exacerbates the adverse effects of F-T cycles on failure deviatoric stress. The strength indices initially decrease and then increase with decreasing freezing temperatures, while they first decrease and then stabilize with an increasing number of F-T cycles. Notably, the deterioration of cohesion is significantly greater than that of the internal friction angle. A quantitative analysis is conducted to examine the relationship between failure deviatoric stress, shear strength index, temperature, and freeze-thaw cycles. The fitting results effectively quantify the influence of different variables on the strength characteristics of loess. The findings of this research have significant theoretical implications for practical engineering applications in the northwest loess region.